The acquisition of Social License to Operate : Create trust through dialogue and receive acceptance - Grimsvik, Tor; Tornberg, Viktor (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2021)
Today, the concept social license to operate (SLO) has been gaining traction among companies. If a company wants to establish a business in a new area or keep their current one, they must cooperate with the stakeholders to acquire and maintain a SLO or be forced to shut down. In the mining and extractive (M&E) sector the negative effects on the environment and local area are so apparent it has made the industry focus on SLO. Previous research draws different conclusions on what factors impact the SLO the most and this presents a research gap to analyze. The purpose of this research is to investigate how companies within the M&E sector need to interact with local communities to build trust and acquire a SLO. This is done by an exploration of how individuals living in or near mining operations perceive mining operations by asking how they feel about the distributional fairness, the procedural fairness, the confidence in governance, the dialogue, the trust towards the mining industry, and the acceptance level towards mining. This research is of a quantitative explanatory character and primary data was gathered from an online questionnaire distributed among two Facebook groups that is connected to Kiruna and Gällivare. A total of 190 responded and their answers were analyzed with the help of statistical techniques. The results indicate dialogue to be an efficient way to communicate for companies towards communities. Procedural fairness and confidence in governance lead to trust while distributional fairness did not and a company that is trusted will receive a SLO.